2013
DOI: 10.1074/jbc.m112.419929
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Elastin Peptide VGVAPG and Human Elastin Binding Protein

Abstract: Background:The interaction of the peptide VGVAPG with the elastin binding protein is critically involved in aneurysm progression.Results: A molecular model of this interaction is proposed and explored using a site-directed mutagenesis strategy. Conclusion: Three residues, Leu-103, Arg-107, and Glu-137, of elastin binding protein are critical players in this interaction. Significance: Our data now allow the design of antagonists of VGVAPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 37 publications
(48 reference statements)
1
51
0
Order By: Relevance
“…31 This polarization of lymphocytes appears to be mediated through a receptor for specific EDPs, since it can be blocked by neutralization of the elastin receptor or with lactose, which causes shedding of the receptor from the cell membrane. 5 Similar treatment inhibited monocyte migration when monocytes were exposed to human AAA tissue extract. 13 A previous study has suggested that EDPs may have an anti-inflammatory effect on macrophages under specific conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 This polarization of lymphocytes appears to be mediated through a receptor for specific EDPs, since it can be blocked by neutralization of the elastin receptor or with lactose, which causes shedding of the receptor from the cell membrane. 5 Similar treatment inhibited monocyte migration when monocytes were exposed to human AAA tissue extract. 13 A previous study has suggested that EDPs may have an anti-inflammatory effect on macrophages under specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Elastin proteolysis releases elastin-derived peptides (EDPs), including peptides with the xGxxPG motif, a commonly repeated sequence in elastin. 5 Of those EDPs released by elastin degradation, the VGVAPG repeat sequence in the human tropoelastin molecule has been shown to have the highest affinity for elastin-binding protein. 58 EDPs are upregulated in the serum of patients with AAA, and an increase in their level is predictive of AAA expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elastin fragments XGXXPG (where X is a generic hydrophobic residue) lead to expression and activation of MMP-1 and MMP-3 in human fibroblasts, suggesting the consensus sequence found in VGVAPG is important for binding to the elastin binding protein (EBP) receptor 36; 37 . This MMP activation in turn worsens local connective tissue damage.…”
Section: Elastin Peptides Are Generation By Mmpsmentioning
confidence: 99%
“…Because of the complex nature of kE, we systematically used the VGVAPG peptide versus a scrambled peptide (VVGPGA) in the following experiments to specifically focus on the ERC in these processes because this peptide is known to bind specifically to the EBP subunit of this receptor. 29,30 Indeed, ≈29 different peptides were identified in kE mixtures by mass spectrometry analysis with one third containing the bioactive GxxPG motif (not shown). 14 In contrast, the scrambled VVGPGA is unable to adopt the type VIII β-turn conformation because of the lack of GxxPG motif.…”
Section: Discussionmentioning
confidence: 99%